2009
DOI: 10.1097/mbc.0b013e32832e05f0
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenols inhibit plasminogen activator inhibitor-1 expression and secretion in endothelial cells

Abstract: Compelling epidemiological evidence suggests that the consumption of green tea is associated with beneficial effects in prevention of cardiovascular diseases. Plasminogen activator inhibitor-1 (PAI-1) is known to play a pivotal role in cardiovascular diseases including arteriosclerosis and hypertension. Increased PAI-1 was found in atherosclerotic lesions, and high PAI-1 plasma levels were associated with coronary heart disease. To determine the effect and molecular mechanism of green tea polyphenols (GTPs) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Bovine aortic endothelial cells (BAECs) were purchased from the Health Science Research Resources Bank (Osaka, Japan). BAECs were cultured at 37°C in 5% CO 2 in Dulbecco minimal Eagle's medium (DMEM) containing 10% fetal bovine serum (Gibco, Grand Island, NY, USA) and 100 mg ml À1 penicillin/streptomycin as described previously (Liu et al, 2009). Confluent cultures (1-5 × 10 6 ) were detached using trypsin/EDTA and collected on 100 mm diameter dishes for further analysis.…”
Section: Cells and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine aortic endothelial cells (BAECs) were purchased from the Health Science Research Resources Bank (Osaka, Japan). BAECs were cultured at 37°C in 5% CO 2 in Dulbecco minimal Eagle's medium (DMEM) containing 10% fetal bovine serum (Gibco, Grand Island, NY, USA) and 100 mg ml À1 penicillin/streptomycin as described previously (Liu et al, 2009). Confluent cultures (1-5 × 10 6 ) were detached using trypsin/EDTA and collected on 100 mm diameter dishes for further analysis.…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…Cells were lysed for 30 min at 4°C in RIPA lysis buffer (Beyotime), and Western blot was carried out as described previously (Liu et al, 2009). All antibodies were used according to the manufacturers' instructions.…”
Section: Western Blotmentioning
confidence: 99%
“…In vivo studies have shown that these green tea extracts appear to have insulin-like activities, with EGCG inhibiting intestinal glucose uptake via the sodium-dependent glucose transporter SGLT1 [61]. In vitro, tea extracts were shown to inhibit endothelial cell plasminogen activator inhibitor-1 (PAI-1; inhibits fibrinolysis and increases the risk of thrombolysis) through a pathway involving PI-3 K/Akt, again, suggesting they may contribute to cardiovascular protection [62]. Other studies have demonstrated that green tea extracts reduced plasma triglycerides, insulin resistance and oxidative stress in insulin-resistant Wistar rats which suggests a potential protective role against diabetes-associated premature development of CVD in patients [63].…”
Section: Evidence For the Protective Properties Of Agext Resveratrolmentioning
confidence: 99%
“…Zhou et al reported that salvianolic acid B attenuates PAI-1 production in human umbilical vein endothelial cells (HUVEC) incubated with tumor necrosis factor α (TNF-α) [9]. Lin et al reported that green tea polyphenols inhibit PAI-1 expression and secretion in endothelial cells [10]. A citrus extract containing flavones represses PAI-1 expression in human colon fibroblasts [11].…”
Section: Introductionmentioning
confidence: 99%